ANALISIS PENGARUH KUALITAS BENANG TERHADAP WAKTU PROSES PRODUKSI KAIN - Rosleini Ria P. Z.; Anita Indrasari; Amar Ma’ruf (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2012)
There is possibility that differences in the quality of raw materials received from the company's suppliers happened. Thus the textile company, the differences of raw materials allows differences in both overall and each stage production process time. From this condition, it is necessary to analyze relationship between quality of raw material and production process time, then the production time can be predicted, and available labor can be optimally allocated. In addition, analysis of this relationship can also be used as guidelines to determine production process time at a certain number of orders based on the thread as raw material quality to be produced. This research used regression analysis, F test, and determination coefficient test. It resulted that both tensile strength and elongation on warping, sizing, weaving and inspecting process influence the change of production time. While in the ricing and folding process, both tensile strength and elongation did not influence the change of production time.